Sobre tecnologias, educação, formação e etnografia: a experiência do Laboratório de Pesquisa Multimeios da Faculdade de Educação (UFC) - Torres, Antonia Lis de Maria Martins (2014)
The work at hand is about an etnographic research done at Laboratório de Pesquisa Muitimeios da Faculdade de Educação [Multimedia Research Lab of Education School] (UFC), which has the following goals: to analyse the construction of the Multimedia Research Lab, its conception and use of digital technology, in the perspective of professors/researchers; to evidence how the Multimedia Research Lab, as a matrix in Exact Sciences, was legitimating itself inside FACED/UFC; to verify the place of this Lab in the formation of its professors/researchers; to identify the specialities of Multimedia in the fields: theoretical-metodological, technical-operative and political in its acting places. The investigation cut of this study was led to the segment professors/researchers bound to the Lab from 1997 to 2012. In the fieldwork it was used things such as observation diary, documental research and semistructured interviews. Data points that this Lab has a conception being guided by the comprehension of the mankind relation with technology in a socio-cultural context, acknowledging technology as a product of mankind, though the ones who create it, elaborate it, but is also modified by it. It was still observed a tentative of “looking” criticly over technology from its uses, beyond the concern in focusing on authors that study technological matters. Beyond that global view, it is noticed that Multimedia has a perspective well directed to the use of digital technology in education, aggregating as a didatic resourse, which can auxiliar not only activities aimed at teaching area, but also activities that involve project elaboration. Nevertheless, it was verified that this conception of technology does not restrict to the aspect of teaching, it extends all the laboratorial activities that we could call “technology philosophy” present at the lab. It was verified the since the Lab constitutes itself as “place to work with technology” in FACED, it makes academic community create expectations that the researchers bound to it also make the work of computer technician. However, there has been tried to demistify that the focus is not technology, but to appropriate of its potencialities aiming at the learning. The testimonials enhanced the conception of the Lab as a place to discuss, to reflect, to try, to give sense to the use of digital technology in education, highlighting that this comprehension was being built in dialogs with theorists of education field. This way, it shows this Lab leaves this dimension more technical to think of the use of technology in education, becoming a place that little by little appropriates itself and being al so appropriated by education, being its big contribution the formative aspect. From the development of its activities, Multimedia has shown its “sense” to the technology in the field of education, to students and researchers that are graduated there. Concerning reflexions of its uses, this is translated in know-how. However, it is highlighted that Multimedia has a digital culture which is self and this happens in the inside of developed practices collectively. The observations indicate that Multimedia as “house of belonging of the subjects”, as also constitutes in changing space, user-friendliness, but also a place marked by dispute and power relation. It was verified that part of this building finds it self pillared in the “figure” of its coordinator, who makes it work, by his way, this Lab. No doubt, this Lab is the fruit of his legacy as product of knowledge involving the fields of math education, computers education, digital inclusion and distance education. It is also possible to infer that one of this Lab especialities is about the concerning of theoretical dimension, because the results of its production is what guarantee its legitimacy and importance in the academic scenary. After the research, it was possible to decipher the reality of Multimedia Lab, looking at it from the outside of a square place, closed walls, full of electronic equipament, many times ”imprisoning” the people in a inside to inside view. This way, we consider that this work allowed the trajectory of this Lab fro m its rupture with a cartesian perspective, routine, reiterative and uniquely burocratic, putting itself face to face with history and the social contemporary processes.